Fetoscopic Laser Ablation of Type II Vasa Previa: A Cost Benefit Analysis - Monson, Martha A.; Chmait, Ramen H.; Einerson, Brett (American Journal of Perinatology, 2023)
Objective We aimed to compare costs of two strategies for third-trimester type II vasa previa management: (1) fetoscopic laser ablation surgery (FLS) referral and (2) standard management (SM).Study Design A decision analytic model and cost-benefit analysis from a health care perspective were performed. The population included patients with type II vasa previa at approximately 32 weeks. SM entailed 32-week antepartum admission and cesarean at approximately 35 weeks. FLS referral included consultation and possible laser surgery at 32 weeks for willing/eligible candidates. Successful laser surgery allowed the possibility of term vaginal delivery. Outcomes included antepartum admission, preterm birth, cesarean, neonatal transfusion, and death. Sensitivity analyses were performed.Results In base case analysis, FLS referral was cost saving compared with SM (total cost per patient $65,717.10 vs. 71,628.16). FLS referrals yielded fewer antepartum admissions, cesareans, premature births, neonatal transfusions, and deaths. Eligible referred patients choosing FLS incurred a total cost of $41,702.46, a >40% decrease compared with SM. FLS referral was cost saving in all one-way sensitivity analyses except when antepartum admission costs were low. In threshold analyses, FLS referral was cost saving unless laser surgery cost was >$39,892 (2.75x expected cost), antepartum admission cost for monitoring of vasa previa or ruptured membranes was <$7,455, <11% patients were eligible for laser surgery, and when <12% of eligible patients chose laser surgery. In two-way sensitivity analysis, FLS referral was cost saving except at very high laser surgery costs and extremely low antepartum admission costs.Conclusion Referral for FLS for type II vasa previa was cost saving and improved outcomes compared with SM, despite upfront costs, fetoscopy-related risks, and many patients being ineligible or not opting for surgery after referral.Key Points
Keywords: vasa previa; fetoscopic laser surgery; type II vasa previa; fetal surgery